Desempenho de serviços de saúde baseado em inquérito de base populacional - Neves, Carlos Magno (2013)
Several authors have sought to understand the variables that shape health services in the SUS and its management, seeking to support the management with information that may contribute to the defragmentation of the system. In this sense the performance of health systems is of major importance for management of this sector. The evaluation of the performance of the health systems is of major importance for the management of the referred sector. With this purpose stands out the population based health surveys, which are being widely used in other countries, and in Brazil they have been gradually used by some government sectors, due to their legitimacy to assess the health status of the population and the health care service provided from the users’ point of view. OBJECTIVE: To analyze the performance of the health services in the municipalities of the northern part of the Integrated Region of Development of the Federal District and surrounding areas from the perspective of the residents. METHODOLOGY: A descriptive epidemiological study using a population-based household survey. An already validated questionnaire was applied, which was submitted to a digital format with the use of an electronic artifact Pocket Hp iPAQ116 The statistical analysis was performed using a SPSS software version 19.0, on which data were crossed and simple frequencies were performed with 95 % confidence interval. RESULTS: From 521 participants, 59.50 % are aged between 18 to 40, 53.93 % are female, being 54.70% of the majority of brown skin color . About the Basic Attention AB1 66.60 % of households were registered in units of the family health, and 33.39 % of residents reported not having health care support, 46.25% residents reported consultation with a physician, 67.63 % of those paid by SUS, also 86.27 % of 51 admissions were provided by SUS, and 82.36 % of the health service users seek predominantly for SUS , and 59.19 % not primarily sought the Primary Care. CONCLUSION: Were recorded a young adult population with a female majority was registered, The provision of health services, are recorded at CNES and enrolls 138 public health services or private contracted by SUS, without however posses or contract a high complexity hospital service, which is presented only in the municipality of Planaltina de Goiás. The gateway service recommended by the federal government to AB, is not perceived as such by the population.